Multiculturalism in History Learning: Students’ Experiences at SMAS Tunas Markatin Jakarta - Andi Andi; Agus Mulyana; Wawan Darmawan; Murdiyah Winarti (Universitas Hamzanwadi, 2025)
Ethnic, cultural, and religious diversity is a distinctive characteristic of Indonesia that can serve as both a strength and a challenge in maintaining social cohesion, particularly in schools where stereotypes, subtle discrimination, and prejudice often disrupt student interactions. This study aims to describe students’ experiences in understanding, internalizing, and practicing multicultural values through history education, as well as to assess the role of schools as transformative spaces for shaping inclusive identities. The research employed a qualitative approach with the Interpretative Phenomenological Analysis (IPA) method, focusing on students’ subjective interpretations of their learning experiences. The participants consisted of 20 students from grade XI and XII at SMAS Tunas Markatin Jakarta as the main subjects, supported by three history teachers, the principal, and teaching documents such as syllabi, lesson plans, and textbooks. Data were collected through semi-structured interviews, classroom observations, and document analysis, and validated through triangulation, member checking, and audit trails. The findings indicate that students perceive multiculturalism not merely as the recognition of differences but as an active attitude of tolerance, empathy, and collaboration in daily life. History teachers play a pivotal role by employing multivocal strategies that incorporate contributions from diverse groups into the historical narrative, enabling students to feel their identities are acknowledged within the nation’s history. Nevertheless, challenges remain in the form of stereotypes and subtle discrimination, particularly related to dialects and cultural practices, which require continuous pedagogical interventions and inclusive school policies. This study highlights that history education plays a strategic role in fostering students’ critical awareness, social solidarity, and inclusive identity in a multicultural society.